2024
DOI: 10.1108/intr-05-2022-0334
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of the metaverse: a laboratory experiment on augmented and virtual reality shopping

Nannan Xi,
Juan Chen,
Filipe Gama
et al.

Abstract: PurposeIn recent years, there has been significant interest in adopting XR (extended reality) technologies such as VR (virtual reality) and AR (augmented reality), particularly in retail. However, extending activities through reality-mediation is still mostly believed to offer an inferior experience due to their shortcomings in usability, wearability, graphical fidelity, etc. This study aims to address the research gap by experimentally examining the acceptance of metaverse shopping.Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 146 publications
0
1
0
Order By: Relevance
“…The study focuses on trust, PU and PEU, which are three important factors for technology adoption. These factors were initially suggested by TAM and later on considered by many other frameworks developed for technology adoption [ 22 , 23 , 25 , [133] , [134] , [135] ]. The purpose of the study is to ascertain how patients and medical professionals assess the use and benefits of metaverse technology in healthcare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study focuses on trust, PU and PEU, which are three important factors for technology adoption. These factors were initially suggested by TAM and later on considered by many other frameworks developed for technology adoption [ 22 , 23 , 25 , [133] , [134] , [135] ]. The purpose of the study is to ascertain how patients and medical professionals assess the use and benefits of metaverse technology in healthcare.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of this research, when people consider the crowdfunding platform to be very useful for paying infaq and alms, they will use the crowdfunding platform to make infaq and alms payments. Empirically, previous research was conducted by Arora et al, (2022) on the intention to use e-hailing applications, Safari et al, (2022) on acceptance of internet banking, Kumari & Devi (2022) on acceptance of Blockchain technology in investing, Kim et al, (2021), Oloveze et al, (2022) discussing online shopping behavior in Nigeria and Xi et al, (2024) acceptance of metaverse for consumers' virtual reality shopping experiences, found that behavioral intention to use technology consistently was strongly influenced by perceived usefulness. Then, the hypothesis formulated is: H3: Perceived usefulness influences behavioral intention to paying infaq and alms through the crowdfunding platform.…”
Section: Perceived Usefulness and Behavioral Intentionmentioning
confidence: 99%